Design and Build It Ticketing Helpdesk Information System At RS. Metropolitan Medical Centre - Nasril; Setiabudi, Arifin; sutriyadi, Riko (ENCRYPTION: Journal of Information And Technology, 2022)
Design and Build an IT Ticketing Helpdesk Information System at the Hospital. Metropolitan Medical Center is a system that can help to provide services in the form of additional requests or feature troubleshooting on existing applications on the RS. Metropolitan Medical Centre. IT Information System Design Ticketing Helpdesk at Hospital. Metropolitan Medical Center comes with features supporters in the form of categories and classifications of requests or requests with different due dates for work selected category. In addition, Design and Build IT Information Systems Ticketing Helpdesk at Hospital. Metropolitan Medical Center uses user leveling system. So, it can help SIRS department staff (Hospital Information System) to manage query data adding or troubleshooting features proposed by staff other units/departments in existing applications. The process of making an IT Ticketing Helpdesk Information System Design on RS. The Metropolitan Medical Center uses the Research Method Development by taking data from RS. Metropolitans Medical Centre, interviewed SIRS department staff, literature review supports problem-solving theory as well as the Unifield Modeling Language (UML) for the design of the application system. This application is web based which can be accessed via Firefox and Google Chrome browser software.